Pancreatic Stump Management Following Pancreatico Duodenectomy- A Tertiary Centre Experience - Dr R Rajamahendran R; Dr Sugaprakash Sankareshwaran; Dr Ramesh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aims: Primary aim is to analyse the outcome of pancreatic stump anastomosis of various types in relation to major morbidities and mortality. Secondary end point of the study is to analyse and compare Isolated PJ technique outcome to conventional methods Methods: Retrospective analysis of prospectively collected data from 2010 to 2014 march on patients underwent Whipple procedure done – 138 patients have undergone Whipple procedure. Patients underwent Pancreatic stump anastomosis have been categorised into three groups. A- PG, B-PJ, C- Isolated PJ. C group later categorised into Dunking type C1 and C2- Duct to mucosa type. Major complications are analysed in relation to anastomotic techniques. Results: When comparing between the three groups undergoing PG, CPJ, IPJ the incidence of delayed gastric emptying in the PG group was 38.46%, the incidence in the CPJ group was 40.98% and in the isolated loop pancreatico jejunostomy group was 44.73%. When comparing the incidence of leak between the three groups it was about 33% in the PG and 29.5% in the CPJ group and 15.78% in isolated PJ group.Duct to mucosa (C1) showed a leak percentage of 9.09% compared to Dunking method (C2) which showed a leak rate of 37.5%. The mortality rate in our study was 5.7%. Conclusion: Among various techniques of pancreas stump reconstruction (PG/PJ /Isolated PJ) none of them showed statistical significant morbidity or mortality of the existing standard. But isolated loop PJ has had statistically significant lower grade leak and increased DGE. Subgroup analysis within the isolated loop has no difference in outcome.